Development of the Digital Transformation Scale: Assessment of Measurement Invariance - Zincirli, Muhammed; Polat, Ebru (Sage Publications Inc, 2025)
The primary aim of this study is to develop a valid and reliable measurement tool that assesses teachers' perceptions of digital transformation. A total of 828 teachers working in public schools in 2 provinces located in the eastern and southern regions of Turkey participated in the study. The construct validity of the scale was tested using exploratory and confirmatory factor analyses (EFA and CFA). According to the EFA results, the scale has a single-factor structure that explains 67.73% of the total variance. The CFA results indicated acceptable fit indices for the single-factor Digital Transformation Scale (DTS). Criterion validity was evaluated using the 21st Century Technology Literacy Skills Scale (TLSS) and the Resistance to Change Scale (RCS), and it was found that the DTS has a positive relationship with the TCTS and a negative relationship with the RCS. Reliability assessments were conducted by calculating the Cronbach's alpha internal consistency coefficient, test-retest method, and composite reliability values across three different samples, all of which exceeded threshold values. The test-retest analysis confirmed the stability of the scale, while the composite reliability analysis supported its reliability. Item analysis was performed using the top and bottom 27% rule and corrected item-total correlations, with both analyses yielding positive results. Additionally, measurement invariance for gender and age variables was established, and the values indicated that measurement invariance was achieved. It was confirmed that the scale provides reliable comparisons between gender and age groups. All these findings support the Digital Transformation Scale as a valid and reliable measurement tool.
Keywords: digital transformation; teacher; measurement invariance; scale development